Emotional Prosody in Interjections: A Case of Non-arbitrariness in Language - Abelin, Åsa (Public Journal of Semiotics, 2013)
Emotional prosody shows a connection between meaning and expression, and constitutes a special case of non-arbitrariness in language. Emotional interjections are learned at an early age, and also have a biological basis for their expression. It is therefore possible that emotional prosody of interjections is part of the phonological and semantic representation in the mental lexicon, and hence can be expected to influence visual lexical decisions. If confirmed, this would have some bearing on the debate concerning the relations between ‘linguistic’ and ‘affective’ prosody. A priming experiment was performed on Swedish interjections with two emotional meanings: HAPPINESS (positive words) and DISGUST (negative words). The main question was whether emotional prosody primes written interjections with emotional content, through cross-modal priming, and the chosen method was to elicit lexical decisions in a cross-modal priming task and in isolation. The results show that there was an effect of priming, and that the effect was significantly greater for HAPPINESS words (and HAPPINESS prosody) than for DISGUST words (and DISGUST prosody). For individual words, there was a positive correlation between a high priming effect for the corresponding emotion and the degree of correct interpretations of emotional primes. Furthermore, there was a tendency for high-frequency words to be primed more than low-frequency words, when the emotion of the prosody was matched. There was no such effect for high-frequency words when the emotion of the prosody was mismatched. There was also a tendency to a negative correlation between degree of correct interpretations of emotional primes and high priming effect, when the prosody was mismatched. We interpret these results to mean that it is problematic to regard emotional prosody as non-linguistic and disconnected from the lexicon, since there was a gradual connection between spoken emotional prosody, written emotional interjections, and lexical frequency of interjections.